Reaksi Pasar Modal Terhadap Kebijakan Investasi, Kebijakan Pendanaan dan Kebijakan Dividen - Ria Angriani (Jurnal Riset Akuntansi, 2023)
This study aims to examine and describe the reaction of capital market (cummulative abnormal return) in investment policy, funding policy and dividend policy. Investment policy is measured using capital expenditure, funding policy is measured by changes in debt to equity ratio (∆DER) and dividend policy is measured by dividend payout ratio (DPR). This research is classified as literature review to provide some information needed by persons related to the company and capital market participants. The study find that almost all research in capital market though cummulative abnormal return are effect by the management policies in investment, funding and dividend.